2(x - 3) = 2x
Cancel 2 on both sides
x - 3 = x
Cancel x on both sides
-3 = 0
Since -3 = 0 is false, there is no solution.
3(y - 3) = 2y - 9 + y
Simplify 2y - 9 + y to 3y - 9
3(y - 3) = 3y - 9
Expand
3y - 9 = 3y - 9
Since both sides equal, there are infinitely many solutions.
10x - 2 - 6x = 3x - 2 + x
Cancel -2 on both sides
10x - 6x = 3x + x
Simplify 10x - 6x to 4x
4x = 3x + x
Simplify 3x + x to 4x
4x = 4x
Since both sides equal, there are infinitely many solutions.
4(x +3) + 2x = x -8
Expand
4x + 12 + 2x = x - 8
Simplify 4x + 12 + 2x to 6x + 12
6x + 12 = x - 8
Subtract x from both sides
6x + 12 - x = -8
Simplify 6x + 12 - x to 5x + 12
5x + 12 = -8
Subtract 12 from both sides
5x = -8 - 12
Simplify -8 - 12 to -20
5x = -20
Divide both sides by 5
x = -20/5
Simplify 20/5 to 4
x = -4
One solution